Az alárendelt nyelve Borbély Szilárd műveiben - Németh, Zoltán (Studia Litteraria, 2016)
The study deals with the possibilities of the subordinate language in the texts of Szilárd Borbély. The theoretical background is provided by the article of Gayatri Chakravorty Spivak Can the subaltern speak?, Marxist philosophy, deconstruction, postcolonial literary theory, cultural studies, feminist literary studies, trauma theory, ecocriticism, multiculturalism and network theory. The paper refers to the change that occured in Hungarian literature and in the works of Szilárd Borbély from around 2000, resulting in the replacement of the ironic-parodic language of literature with the traumatic. The subordinated language of the works of Szilárd Borbély can be approached as a poetics of silence, communication disorders, speech impediments, aphasia, a voice disorder, stuttering, the anarthria, dysarthria, apraxia, mutism etc., as well as a dialect and the poetics of error. The grammatical and stylistic errors of the texts result in a tragic and traumatic effect.